Transcriptome study reveals apoptosis of porcine kidney cells induced by fumonisin B1 via TNF signalling pathway. (May 2020) - Chen, Jia; Yang, Shuhua; Huang, Sheng; Yan, Rong; Wang, Mingyang; Chen, Si; Cai, Jing; Long, Miao; Li, Peng
Abstract: Fumonisin B1 (FB1 ) is a mycotoxin that contaminates cash crops and has toxic effects on humans and livestock. However, the toxic effect of FB1 is not fully understood. In this study, the apoptosis mechanism of FB1 on porcine kidney cells (PK-15) was elucidated by transcriptome analysis. The results showed that FB1 observably changed the expression of mRNA in PK-15 and induced the cells of apoptosis after being exposed to 106 μM FB1 in vitro. Gene Ontology and KEGG enrichment analyses showed that FB1 exposure increased the expressions of related mRNA in TNF signalling pathway in PK-15. To verify our bioinformatics analysis, these changes were verified by qRT-PCR and Western blot assay. Furthermore, the mRNA expressions of NF-κB and its downstream genes or proteins decreased significantly ( p  < 0.01) after the addition of BAY11-7082, the inhibitor of NF-κB. Therefore, for the first time, we demonstrate that FB1 can induce apoptosis of PK-15 cells through TNF signalling pathway, and NF-κB gene is a target of FB1 acting on the TNF signalling pathway. Highlights: Screen for differential genes related to FB1 toxicity. Apoptosis of FB1 on porcine kidney cells through TNF pathway. NF-κB target participates in TNF signalling pathway to induce apoptosis.